Strategic planning in turbulent environments: a social ecology approach to scenarios - Ramírez, R; Selsky, JW (Elsevier, 2014)
We contrast conventional strategic approaches derived from neoclassical economics with a socio-ecological approach to strategy. We propose that the socio-ecological approach, and specifically the causal textures theory of organizational environments it spawned, helps strategic planners to better engage the unpredictable uncertainty that characterizes turbulent environments. To support our argument, we render explicit three principles that have been implicit in causal textures theory. We articulate general strategic planning stances for organizations consistent with each of the three principles, and demonstrate how scenario planning can help to instantiate each principle. We conclude that causal textures theory helps strategic planners to better understand the purpose of scenario planning and helps to guide them on how to make use of scenario planning to effect better strategies in a turbulent environment.